Assessing early-onset hallucinations in the touch-screen generation. (March 2015) - Demeulemeester, Morgane; Kochman, Fréderic; Fligans, Benjamin; Tabet, Ahmed J.; Thomas, Pierre; Jardri, Renaud
Summary: The increasing development of apps for digital devices provides an opportunity for new instruments to assess hallucinations in young individuals. Here we present the Multisensory HAllucinations Scale for Children (MHASC), dedicated to assessing complex early-onset hallucinations. The MHASC will soon be translated into multilanguage versions with the support of the International Consortium of Hallucination Research.